Performance of Regional Staffing Agency Services in order to Increase the Rank of Civil Servants of Murung Raya Regency of Central Kalimantan - Yanson Dion (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
This research aims to describe and analyze the performance of services and what factors affect the service performance of the Regional Staffing Agency in the framework of the promotion of Civil Servants of the Regional Staffing Agency in the framework of the promotion of Civil Servants in Murung Raya Regency. The approach taken in this study is a qualitative approach with the instrument is an interview. Measured, as well as documents that support the author in using informant data in this study amounted to 15 people consisting of Employees at the Regional Staffing Agency of Murung Raya Regency. The results of the Regional Staffing Agency's service performance research in terms of promotions seen from productivity, service quality, responsiveness, responsibilities and accountability in Murung Raya Regency have been good. That is, from the receipt of files, file verification, management to BKN Regional Kalimantan to the issuance of the promotion decree is basically in accordance with the regulations, in accordance with the vision of BKD's mission and provides good satisfaction to the community of service users (PNS) of Murung Raya regency. The performance of promotion services in BKD Murung Raya which is an obstacle factor such as changing rules about the technical requirements of promotion, there are still some civil servants who are late to submit their files or files submitted incomplete and the distance between BKD and BKN Regional Banjarbaru so that the enactment is scheduled earlier or faster.